Assessment of Reproductive Performance and Husbandry Practices of Horro and Crossbred Cattle Under Smallholder in Sibu Sire District of East Wollega Zone, Oromia, Ethiopia - Abriham Kebede Deresa; Jiregna Dugassa Kitessa; Yobsan Tamiru Terefa (Veterinary Medicine and Science)
ABSTRACT Purpose The reproductive and production performance of dairy cows determines the profitability of a dairy farm. Method A questionnaire survey was used to assess reproductive performance and husbandry practices by using 100 randomly selected animal owners. Result Seventy‐nine percent of animal owners involved were men, ages between 30 and 60. Their education was as follows: 26% were illiterate, 67% in primary school and 7% in secondary school. Ninety‐five percent of them managed their animals extensively and used natural mating and breeding practices (75%). AFS in months were 46.83 ± 0.65 in Ada‐Buke Warego, 46.00 ± 1.36 in Hagalo‐Tulam, 47.08 ± 0.99 in Dicho Aba‐Garmama and 47.29 ± 0.51 in Waligalte. AFC in months were 56.68 ± 0.97 in Ada‐Buke Warego, 58.00 ± 1.36 in Hagalo‐Tulam, 57.23 ± 1.41 in Dicho Aba‐Garmama and 56.24 ± 1.13 in Waligalte. ANSPCs were 1.85 ± 0.08 in Ada‐Buke Warego, 1.67 ± 0.14 in Hagalo‐Tulam, 1.54 ± 0.14 in Dicho Aba‐Garmama and 2.00 ± 0.10 in Waligalte. The mean length of CI in months was 30.88 ± 0.90 in Ada Buke Warego, 29.00 ± 1.68 in Hagalo‐Tulam, 28.62 ± 1.62 in Dicho Aba‐Garmama and 31.06 ± 1.04 in Waligalte. The average year of longevity was 9.22 ± 0.7 in Ada‐Buke Warego, 9.08 ± 0.8 in Hagalo‐Tulam, 9.31 ± 0.13 in Dicho Aba‐Garmama and 9.21 ± 0.8 in Waligalte, but there is no significant association (p ≥ 0.05). AFC in months was 48.00 ± 0.00 in local and 37.20 ± 1.30 in crossbreeds. ANSPC was 1.92 ± 0.06 in locals and 1.10 ± 0.10 in hybrids. AFC for Horro and crossbred dairy cattle were 57.73 ± 0.59 and 48.00 ± 0.00 months, respectively. The mean length of CI was 30.53 ± 0.67 and 29.40 ± 1.99 months in natives and crossbreeds, respectively. The average year of longevity was 9.22 ± 0.05 and 9.10 ± 0.10 years for local and hybrids, respectively. ANSPC for natural mating and AI were 1.92 ± 0.05 and 1.10 ± 0.10, respectively, with significant association (p < 0.05). Conclusion The reproductive performance of dairy cows in the study area was low, which required the improvement of husbandry practices.